Anti-Alzheimer’s and Anti-Fungal Activities of Pyrrolo[1,2-a] Quinoline Derivatives: Pharmaceutical Science-Chemistry - N Patil, Pramod; Uppar, Vijayakumar; Padmashali, Basavaraj; Keri, Rangappa (International Journal of Life Science and Pharma Research, 2023)
Psychiatrists have described the protein deposits in the brain that causes various diseases such as cerebral, functional,physiological dysfunction, and neurodegenerative diseases. Although Alzheimer's disease is detectable, its treatment remainsunattainable. More than 4.6 million new patients are recorded yearly, who are affected by Alzheimer's disease and only a fewdrugs are currently in use for treatment with side effects. Hence, there is a clinical need for new drugs, design, and development.On the other hand, despite the development of antifungal therapeutics over the last three decades, antifungal resistance is still amajor cause. Regularly using inappropriate antimicrobials has become a major healthcare problem globally in the 21st century andhas been titled a "silent tsunami facing modern medicine." It has been estimated that over 8,000,000 die yearly, which providesscope for developing novel antifungal drugs. In this research paper, we describe the synthesized dimethyl-1-(4-substitutedbenzoyl)-5-methylpyrrolo[1,2-a] quinoline-2,3-dicarboxylate 1a-c and ethyl-1-(4-substituted benzoyl) 5-methylpyrrolo[1,2-a]quinoline-3-carboxylate 1d-f were evaluated for in vitro antifungal and anti-Alzheimer’s activities. The derivatives1a-f wereobtained by 1,3-dipolar cycloaddition reaction by treating quaternary salt with dimethyl acetylene dicarboxylate and ethylpropiolate respectively, in the presence of K2CO3 and DMF as a solvent. Among all compounds, 1a, 1d, and 1e showed thehighest inhibitory capacity with IC50 values of 0.28, 0.32, and 0.30 μM, respectively. On the other hand, derivatives were alsoscreened for antifungal activity that displayed moderate activity, whereas 1a and 1f derivatives showed good activity.